2003
DOI: 10.1186/1472-6750-3-3
|View full text |Cite
|
Sign up to set email alerts
|

Crude extracts of bacterially expressed dsRNA can be used to protect plants against virus infections

Abstract: Background: Double-stranded RNA (dsRNA) is a potent initiator of gene silencing in a diverse group of organisms that includes plants, Caenorhabditis elegans, Drosophila and mammals. We have previously shown and patented that mechanical inoculation of in vitro-transcribed dsRNA derived from viral sequences specifically prevents virus infection in plants. The approach required the in vitro synthesis of large amounts of RNA involving high cost and considerable labour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(117 citation statements)
references
References 36 publications
(56 reference statements)
1
113
0
3
Order By: Relevance
“…Recent studies have shown that bacterially produced dsRNA could interfere with virus infection [13,[30][31][32]. As a means of acquiring transgenic plants, using dsRNA transcripts provided by this strategy for RNA interference has apparent advantages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that bacterially produced dsRNA could interfere with virus infection [13,[30][31][32]. As a means of acquiring transgenic plants, using dsRNA transcripts provided by this strategy for RNA interference has apparent advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of hpRNAs in bacterial extracts were confirmed by treatment with 100 μg/mL RNase A under high salt conditions (0.3 mol/L NaCl, 0.03 mol/L sodium citrate) for 37°C, 1 h. Then, the dsRNAs were purified by gel-extraction, and reverse transcriptase PCR plus sequencing was done to make sure that the expressed dsRNAs have correct sequences. The correct strains were used to produce hpRNAs according to the method of Tenllado et al [13].…”
Section: Induction and Extraction Of Hprnasmentioning
confidence: 99%
See 1 more Smart Citation
“…The nontransgenic dsRNA approach, as confirmed in both a dicot plant (tobacco) and a monocot plant (maize), provided the possibility to protect a variety of crops from a diverse group of plant viruses (Gan et al 2010). However, in contrast to the heritable resistance mediated by transgene RNA silencing, the transient approach did not confer long-term protection (Tenllado et al 2003). Therefore, continuous spraying is required for the maintenance of protection.…”
Section: Biosafetymentioning
confidence: 98%
“…Meanwhile, another study found that a bacterial strain lacking the dsRNA-specific endonuclease RNase III could be cultured to produce high levels of specific dsRNAs, and those dsRNAs could effectively trigger strong and gene-specific gene silencing when fed to Caenorhabditis elegans (Timmons et al 2001). Subsequently, this method was designed for bacterial systems to biosynthesize dsRNA in vivo, and crude extracts were inoculated into plants via spraying onto plant surfaces (Tenllado et al 2003). More studies on nontransgenic approaches were conducted, including producing dsRNA using different dsRNA prokaryotic expression systems ), resistant efficiency mediated by dsRNA derived from different viral function genes (Sun et al 2010b), and different regions of the same gene (Sun et al 2010a).…”
Section: Biosafetymentioning
confidence: 99%